PENGARUH KOMPENSASI DAN FLEKSIBILITAS KERJA TERHADAP KEPUASAN KERJA DRIVER GOJEK DI PONTIANAK - Adjie, Wisnu Sindhu B1021161118 (Jurnal Manajemen Update, 2020)
This study aims to examine and analyze the Effect of Compensation and Work Flexibility on Job Satisfaction Gojek Driver in Pontianak. In this study, the population is all Gojek drivers in Pontianak. The sample in this study amounted to 100 respondents using a sampling technique that is Accidental Sampling (Convenience sampling) and the data analysis model used is Multiple Linear Regression Analysis. Based on research results show that compensation and work flexibility can explain its effect on job satisfaction. The results of this study indicate that the compensation and work flexibility variables have a positive and significant effect on job satisfactionKeywords: Compensation, Work Flexibility, and Job SatisfactionAndreas. (2015). Manajemen Sumber Daya Manusia. Jakarta: Gramedia Pustaka Utama.Baeza, M. A., Gozalez, A. J., & Wang, Y. (2018). Job flexibility and job satisfaction among Mexican professionals: a socio-cultural explanation. Employee Relations. https://doi.org/10.1108/ER-12-2016-0236.Bangun, W. (2012) Manajemen Sumber Daya Manusia. ErlanggaCarlson, D. S., Grzywacz, J. G., & Kacmar, K. M. (2010). The Relationship of Schedule Flexibility and Outcomes via the Work–Family Interface. Journal of Managerial Psychology. 25. 330-355.Ghozali, I. (2011). Aplikasi Analisis Multivariat Dengan Program SPSS. Semarang: Badan Penerbit Universitas DiponegoroDataboks. (2018). Aplikasi Transportasi Online Paling Banyak Digunakan. Diakses dari https://databoks.katadata.co.id/datapublish/2018/02/12/go-jek-aplikasi-transportasi-online-paling-banyak-digunakanHandoko, T. H. (2001) Manajemen Personalia dan Sumber Daya Manusia, Edisi Kedua. BPFE, Yogyakarta.Hasibuan, M. (2014). Manajemen Sumber Daya manusia. Jakarta: Bumi Aksara.Hill, E. J., Grzywacz, J. G., Allen, S. M, Blanchard, V. L., Matz, C., Shulkin, S., & Pitt-Catsouphes, M. (2008). Defining and conceptualizing workplace flexibility. Community, Work & Family, 11 (2): 149-163.Hofacker, D., & Konig, S. (2013). Flexibility and Work-Life Conflict in Times of Crisis: A Gender Perspective. International Journal of Sociology and Social Policy. Vol. 33.Hooks & Higgs, J. L. (2000). Changing Environment and Productivity Relationships in Professional Services Firms, Working Paper, Florida Atlantic UniversityKamaluddin. (2003). Ekonomi Transportasi, Jakarta: Ghalia IndonesiaKreitner, R & Kinicki, A. (2012). Perilaku Organisasi. Jakarta: Salemba Empat.Lewis, S. & Humbert, A. L. (2010). Discourse or reality? Work-life balance, flexible working policies and the gendered organization. Equality, Diversity and Inclusion: An International Journal. 29. 239-254.Luthans, F. (2011). Organizational Behavior: An Evidence-Based Approach New York: McGraw-Hill.Mabaso, C.M, & Dlamini, B.I (2017). Research Article Impact of Compensation and Benefits on Job Satisfaction, Research Journal of Business Management, 11 (2): 80-90.Malik, M. E., Ghafoor, M. M., & Iqbal, H. K. (2013). Impact of Job Overload and Work Schedule Flexibillity on Job Satisfaction: An Insight in Education and Banking Sector of Pakistan. International Review of Social Sciences and Humanities, 5 (1), 38-47.Mangkunegara, A. P. (2011). Manajemen Sumber Daya Manusia Perusahaan Bandung: RosdaMuguongo, M. M., Muguna, A.T., & Muriithi, D.K. (2015). Effects of Compensation on Job Satisfaction Among Secondary School Teachers in Maara Sub - County of Tharaka Nithi County, Kenya, Journal of Human Resource Management, (6): 47-59.Muhaimin. (2004). Hubungan Antara Kepuasan Kerja Dengan Disiplin Kerja Karyawan Operator Shawing Computer Bagian Produksi Pada PT. Primarindo Asia Infrastruktur TBK Bandung. Jurnal Psikologi Universitas Bina Darma.Mulawarman. (2019, 3 September). Penjelasan Gojek terkait aksi driver gojek pontianak mogok kerja. diambil dari. https://pontianak.tribunnews.com/amp/2019/09/03/penjelasan-gojek-terkait-aksi-driver-gojek-pontianak-mogok-kerja-tuntut-kebijakan-tarif-insentif.Murty, W. A., & Hudiwinarsih. G. (2012). Pengaruh Kompensasi, Motivasi Dan Komitmen Organisasional Terhadap Kinerja Karyawan Bagian Akuntansi (Studi Kasus Pada Perusahaan Manufaktur di Surabaya). The Indonesian Accounting Review Volume 2, No. 2,Origo, F., & Pagani, L. (2008). Workplace flexibility and job satisfaction: some evidence from Europe, International Journal of Manpower, Vol. 29 No. 6, 539-566.Priyatno, D. (2010). Paham Analisa Statistik Data Dengan SPSS. Mediakom, Yogyakarta.Rivai, V. (2011). Manajemen Sumber Daya Manusia untuk Perusahaan: dari Teori ke Praktik, Jakarta: RajaGrafindo Persada.Robbins, S. P. (2006). Perilaku Organisasi edisi kesepuluh. Jakarta: Indeks.Russia Beyond. (2019). Resahkan kompetitor: Maxim. Diakes dari https://id.rbth.com/economics/81796-maxim-ojol-asal-rusia-wyxSanusi, A. (2011). Metodologi Penelitian Bisnis. Jakarta: Salemba Empat.Sekaran, U. & Bougie, R. (2013). Research Methods for Business. United Kingdom: Jhon Wiley & Sons Ltd.Selby, C., & Wilson, F. (2003) Handbook of flexible working. New York Plenum Press.Simamora, B. (2005). Analisis Multivariate Pemasaran. Jakarta: PT. Gramedia Pustaka Utama.Solanki, K. (2013). Association of Job Satisfaction, Productivity, Motivation, Stress Levels with Flexible time. Journal of Organisation & Human Behavior, Volume 2.Sopiah. (2013). The Effect of Compensation toward Job Satisfaction and Job Performance of Outsourcing Employees of Syariah Banks in Malang Indonesia, International Journal of Learning & Development, Vol. 3.Sugiyono. (2016). Metode Penelitian Kuantitatif, Kualitatif dan R&D. Bandung: AlfabetaSupriyanto, A. S, & Darma, P. S. (2017). The Effect of Compensation On Satisfaction And Employees Performance, Management and Economics Journal, Volume 1, Issue 1.Wibowo. (2014). Manajemen Kinerja. Jakarta: Rajawali PersWidiyanto, I. (2008). Pointers: Metodologi Penelitian. Semarang: BP UndipWikipedia. (2019). Grab (perusahaan), Anterin, Gojek. Diakses dari https://id.wikipedia.org/Winda, O., Nayati, U.H, & Arik, P. (2017). Impact of Compensation and Career Development on Job Satisfaction and Employees Performance, RJOAS, 4(64).Yamoah, E.E. (2014). Exploratory Analysis of Compensation and Employee Job Satisfaction, Developing Country Studies, Vol.4, No.12.